Negociações de ganhos mútuos: um estudo de caso na empresa pública delta - Ramos, Vitor Hugo da Costa (2009)
Negotiation is the most efficient tool to achieve something you want, it occurs when there are conflicts and alternatives to be selected that can involve the whole company. The various alternatives have common and conflicting interests, expressing the complexity of relationships. With the increasing demand for agility in responding to the new profiles to search, organizations need to be more versatile in the process and faster to react to market changes, and the Negotiation of Mutual Gains (NMG) are a current driving value-creation. This dissertation aims to propose the use of tools of the theory of the NMG for the managers as a tool supporter of public purchases purchasers of products and services at IT to achieve the expected results. For this, we performed a search of a descriptive and exploratory using qualitative approach. To achieve this objective, theoretical studies were made of themes: Organizational Flexibility, Management of Public Procurement, Information Systems, Strategic Alignment and theory of negotiation in order to get a better understanding of the research. It was not drawn up a structured questionnaire, the research instrument used in this study. Applied the questionnaire directly to participants, it was obtained a participation of 10 respondents, all of participating in public bidding processes Delta. Once performed the data collection, the responses were analyzed using a form of the technique of content analysis, called pattern-matching in order to compare the results with the theoretical framework used in the study. As a result of the study, it was identified using the distributive approach in bidding processes.